MORPHOLOGY AND SEDIMENTARY PROCESSES ON THE CONTINENTAL SLOPE OFF PINE ISLAND BAY, AMUNDSEN SEA, WEST ANTARCTICA - Dowdeswell J.A.; Evans J.; O'Cofaigh C.; Anderson J.B. (My University, 2006)
Morphology and sedimentation on the Pine Island Bay continental margin, eastern Amundsen Sea, is investigated using swath bathymetry, parametric subbottom profiler (TOPAS) records, and sediment cores. A major cross-shelf trough extends to the continental shelf edge at 114°W, through which fast-flowing ice drained the West Antarctic Ice Sheet under full-glacial conditions. The slope adjacent to the trough mouth is 4°, whereas to the east and west it is steeper. A bulge in bathymetric contours beyond and east of the trough mouth indicates some slope progradation. Elsewhere, seismic-reflection profiles indicate major shelf aggradation and minor slope progradation. Networks of gullies and channels dominate the slope adjacent to Pine Island Bay. In front of the trough mouth, gullies at the shelf edge and uppermost slope connect directly with channels that continue to the continental rise. Other gullies connect indirectly with channels further downslope. TOPAS records indicate that gully-channel systems acted as conduits for coarse-grained sediment transfer. Cores comprise turbidites representing channel deposits and diamicton facies deposited by debris flows. Sandy turbidites interbedded with hemipelagic muds occur on the rise and abyssal plain. The West Antarctic Ice Sheet extended to the shelf edge during full glacials, delivering water-saturated till and turbid water directly to the continental slope along a line source. Gully-channel systems are probably a product of sediment gravity flows derived from the release of water-saturated till and turbid water along the ice-sheet margin, perhaps augmented subsequently by downslope flow of dense cold and saline water associated with sea-ice production during the Holocene. The gully-channel systems enable sediment to bypass the continental slope. Spatial variations in gully-channel system morphology along the Amundsen Sea continental slope are probably linked to differences in sediment gravity flow processes and the rate and composition of sediment delivered to the shelf edge from the ice sheet. Cored sediments on the slope and abyssal plain record the widespread presence of turbidite sands, indicating that downslope transfer of glacier-derived sediments has taken place. This supports our interpretation that submarine channels are derived from, and are conduits for, mass wasting. Submarine channels on the upper slope continue into the abyssal plain as far north as ~67°S. They are separated by sediment drifts and sediment waves resulting from the interaction between downslope turbidity current processes and along-slope bottom currents. Similar deep-sea sedimentary processes operate along much of West Antarctica and the western side of the Antarctic Peninsula. © 2006 Geological Society of America.
Keywords: AMUNDSEN SEA; CONTINENTAL SLOPE; GULLIES; ICE STREAMS; PINE ISLAND BAY; SUBMARINE CHANNELS; TURBIDITES; WEST ANTARCTIC ICE SHEET; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен